Phenology of Alpine Plants in the Valley of Flowers National Park and Hemkund, Western Himalaya - Kala, Chandra Prakash (Indian Forester, 1999)
Phenology of alpine plants was studied in the sub-alpine and alpine zone of the Valley of Flowers National Park and Hemkund, located in the Western Himalayas. Transects were laid in both the areas and monitored for phenology at every 30 days interval. A total of 95 flowering plant species were found on the transects, of which 84% were forbs, 14% were evergreen shrubs and undershrubs, and remaining 2% were grasses and sedges. The vegetative phase peaked in June and from the same month flowering phase also increased in the valley. July and August were the best months for flowering. The prominent vegetative phase peaked earlier (in June) in the cushion forming forbs than in other forms. The growing season was longest at lower altitudes and decreased with increasing altitude from sub-alpine forest to alpine meadows.